Volume 2C: Turbomachinery 2018
DOI: 10.1115/gt2018-75982
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Resolving Simulations of Low-Pressure Turbine Cascades With Wall Roughness Using a Spectral-Element Method

Abstract: The accurate prediction of wall-roughness effects in turbomachinery is becoming critical as turbine designers address airfoil surface quality and degradation concerns arising from the shift to advanced ceramic matrix composite (CMC) or additively-manufactured airfoils operating in higher temperature environments. In this paper, a recently developed computational capability for accurate and efficient scale-resolving simulations of turbomachinery is extended to analyze the boundarylayer separation and transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…Variable spatial order can be specified over the domain [27]. The solver was validated up to 16 th spacial and temporal order with highly separated turbulent flows [28,29]. Surface roughness is generated using the methodology proposed in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Variable spatial order can be specified over the domain [27]. The solver was validated up to 16 th spacial and temporal order with highly separated turbulent flows [28,29]. Surface roughness is generated using the methodology proposed in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Garai et al [31] used a spectral element discontinuous Galerkin method with up to 16th order accuracy to conduct scale-resolving simulations of an HPT cascade, with focus on comparing natural transition occurring with clean inflow and bypass transition triggered by turbulent inflow. They reported that the turbulent characteristics of the vane boundary layers differed depending on whether the flow had undergone natural or bypass transition.…”
Section: High-pressure Turbinementioning
confidence: 99%
“…Complete details of this test case and the effects of surface roughness are presented in an upcoming article. 25…”
Section: B Low Pressure Turbine Cascadementioning
confidence: 99%